Gjellestad introduction, background and historical framework - Knut Paasche; Kjetil Loftsgarden; Christian Løchsen Rødsrud (Viking)
The spark that ignited this research project was the discovery of the Gjellestad ship in the autumn of 2018 by the Norwegian Institute for Cultural Heritage Research (NIKU). The surveying was initiated by Østfold County Council (ØCC) after a landowner planned to drain farmland (Figure 1). Archaeologists Lars Gustavsen and Erich Nau, both associated with NIKU, conducted the geophysical surveys that led to the uncovering of this amazing archaeological find.